Human heterologous liver cells transiently improve hyperammonemia and ureagenesis in individuals with severe urea cycle disorders - Meyburg, Jochen; Opladen, Thomas; Schenk, Jens-Peter; Schmidt, Jan; Weitz, Jürgen; Okun, Jürgen G.; Bürger, Friederike; Kölker, Stefan; Hoffmann, Georg F. (Journal of inherited metabolic disease, 2018)
BackgroundUrea cycle disorders (UCDs) still have a poor prognosis despite several therapeutic advancements. As liver transplantation can provide a cure, liver cell therapy (LCT) might be a new therapeutic option in these patients.MethodsTwelve patients with severe UCDs were included in this prospective clinical trial. Patients received up to six infusions of cryopreserved human heterologous liver cells via a surgically placed catheter in the portal vein. Portal vein pressure, portal vein flow, and vital signs were monitored continuously. Calcineurin inhibitors and steroids were used for immunosuppression. In four patients, ureagenesis was determined with stable isotopes. Number and severity of hyperammonemic events and side effects of immunosuppression were analyzed during an observation period of up to 2 years.ResultsNo study-related mortality was observed. The application catheter dislocated in two children. No significant side effects of catheter application or cell infusion were noted in the other ten patients. The overall incidence of infections did not differ significantly from a historical control group, and no specific side effects of immunosuppression were found. Seven patients were treated per protocol and could be analyzed for efficacy. Severe metabolic crises could be prevented in all of these patients, moderate crises in four of seven. Ureagenesis increased after cell infusion in all patients investigated.ConclusionsWe found a favorable safety profile with respect to catheter placement, intraportal liver cell infusion, and immunosuppression. More than half of the children treated per protocol experienced metabolic stabilization and could be safely bridged to liver transplantation.
First online: 12 October 2017
Gesehen am 28.11.2018